Sustainable Composite Construction Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Often, a project's sustainability is centred on building services and energy, but we need to have a comprehensive view of how we integrate deeper sustainability. Traditionally, we have neglected embodied carbon generated during building construction, which has led to significant carbon emissions over the last few decades, causing global warming and other related problems. The aim of this Special Issue was to collect the results of research and practice experiences in sustainable building structures, made from steel, concrete, timber, and other composite materials. Dr Roy and Dr Ananthi warmly invited authors to submit their papers for potential inclusion in this Special Issue of “Sustainable construction using steel, concrete, timber, and other composite materials”, in the journal of Journal of Composites Science.